2017
DOI: 10.1177/1077559517729479
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Abuse Prevention Opportunities: Parenting, Programs, and the Reduction of Risk

Abstract: To date, child sexual abuse (CSA) prevention has relied largely on child-focused education, teaching children how to identify, avoid, and disclose sexual abuse. The purpose of this article is to explore how prevention opportunities can include parents in new and innovative ways. We propose that parents can play a significant role as protectors of their children via two pathways: (i) directly, through the strong external barriers afforded by parent supervision, monitoring, and involvement; and (ii) indirectly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
68
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 86 publications
(143 reference statements)
5
68
0
14
Order By: Relevance
“…These prevention approaches inform the needed unique prevention strategy in two important ways: parents cannot be expected to voluntarily attend yet another prevention program and short, one-time programs can be effective in improving parent knowledge and behavior. Rudolph et al (2018) suggested the utility of embedding a CSA module into existing evidence-based parent education (PE) programs. PE programs are designed to modify knowledge, attitudes and behaviors about child development, increase positive parent-child interactions, improve parental mental health symptoms and reduce problem behaviors exhibited by the child (Lundahl, Nimer, & Parsons, 2006;Timmer & Urquiza, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…These prevention approaches inform the needed unique prevention strategy in two important ways: parents cannot be expected to voluntarily attend yet another prevention program and short, one-time programs can be effective in improving parent knowledge and behavior. Rudolph et al (2018) suggested the utility of embedding a CSA module into existing evidence-based parent education (PE) programs. PE programs are designed to modify knowledge, attitudes and behaviors about child development, increase positive parent-child interactions, improve parental mental health symptoms and reduce problem behaviors exhibited by the child (Lundahl, Nimer, & Parsons, 2006;Timmer & Urquiza, 2014).…”
mentioning
confidence: 99%
“…This is not surprising as CSA is distinct from other forms of maltreatment in meaningful ways for prevention efforts. CSA, like other forms of maltreatment, is likely to occur under a confluence of individual and contextual factors such as parental substance use, parental mental illness, or poor parent-child relationships (Rudolph et al, 2018). However, distinct environmental risk factors contribute to perpetration of CSA, making it possible to identify unique targets for CSA prevention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The United States has established a comprehensive array of health promotion and CPA prevention resources, services, and policies. It has allocated funding to implement policies and provide services and resources (e.g., Fortson et al 2016; U.S. Department of Health and Human Services 2016; Rudolph et al 2018). The United States and its citizens are committed to CPA prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The United States has developed a comprehensive array of child abuse and neglect (CAN) prevention resources and has allocated funding to provide these resources (e.g., Forston et al 2016;Rudolph et al 2018;U.S. Department.…”
Section: Introductionmentioning
confidence: 99%